A New Class of 1,2,4-Triazolo-Benzothiazole Hybrids as Promising Antibacterial Agents - Honnalli, Suresh S.; Hampannavar, Girish A.; Gatibyali, Iranna S. (Asian Journal of Chemistry, 2026)
A novel series of 1,2,4‑triazolo‑benzothiazole derivatives (6a-l) were designed, synthesised and evaluated for antimicrobial activity. The synthesis proceeded through multistep construction of the triazolo‑benzothiazole core from m‑chloroaniline, followed by functionalisation with substituted aromatic and heterocyclic amines. Structures were confirmed by IR, NMR and mass spectrometry. Antibacterial screening against Gram‑positive (S. aureus, B. subtilis) and Gram‑negative (E. coli, P. aeruginosa) strains employed cup‑plate and serial‑dilution assays. Compounds 6a, 6e and especially 6h displayed broad‑spectrum potency, with 6h active at low concentrations. Molecular docking showed strong binding where, 6e scored -10.8 kcal/mol against S. aureus (PDB 5CPQ) and 6d scored -10.5 kcal/mol against E. coli (PDB 5TZ1), surpassing ciprofloxacin (-8.0 and -8.5 kcal/mol, respectively). Interactions involved multiple hydrogen bonds and extensive hydrophobic contacts. ADMET profiling indicated compliance with Lipinski’s rule of five, high gastrointestinal absorption, low toxicity risk and no blood‑brain barrier penetration, supporting their potential as orally active antimicrobial agents.